Three-dimensional analysis of hip and knee joint movements during dolphin kicking and butterfly swimming - Yamakawa, K. K.; Takagi, H.; Sengoku, Y. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The aims of this study were to clarify differences in hip and knee joint movements during dolphin kick alone and during butterfly stroke swimming, and to investigate which parameter relates to swimming performance in each stroke. Eight male swimmers performed three trials using dolphin kick with a kick board (BD), underwater dolphin kick (UD), and butterfly swimming (Fly) at 80% maximal effort in a water flume. Three-dimensional coordinates of the swimmers during the trials were obtained using a motion capture system, and these coordinates were used to calculate the horizontal velocity of the hip (Vhip), the hip and knee joint angle, and the angular velocity. Butterfly kicking motion was divided into first kick (Fly-1st) and second kick (Fly-2nd) according to the stroke phase, and the kinematic parameters during the 4 different kicks were used for analysis. As the main results, it was indicated that the peak hip flexion angle during Fly-2nd was significantly smaller than that during BD and UD (BD, -27.8 ± 9.7 deg; UD, -27.7 ± 10.5 deg; Fly-1st, -25.6 ± 13.9 deg; Fly-2nd, -16.2 ± 7.0 deg, p < .05) and the peak knee extension angle during Fly-2nd was significantly smaller than that during BD, UD, and Fly-1st (BD, -7.6 ± 5.8 deg; UD, -4.4 ± 5.7 deg; Fly-1st, -7.4 ± 4.9 deg; Fly-2nd, 2.0 ± 6.6 deg, p < .05). The mean Vhip during BD was significantly correlated with the peak hip external rotation angle (r = -0.77), the peak knee extensionangle (r = -0.77), the peak hip external rotation angular velocity (r = -0.88) and the peak knee flexion angular velocity (r = 0.81). The mean Vhip during UD was significantly correlated with the peak knee extension angle (r = -0.87), the peak hip external rotation angular velocity (r = -0.73) and the peak knee flexion angular velocity (r = 0.95). The mean Vhip during Fly was not correlated with any of the kinematic parameters during Fly-1st and Fly-2nd. Our results demonstrate that flexion/extension movements of the hip and knee joint are different between dolphin kick and butterfly swimming. Furthermore, larger knee extension, greater hip external rotation velocity, and greater knee flexion velocity may be important to increase dolphin kick performance.